IDENTIFIKASI POLA DEMOGRAFI DI PROVINSI JAWA BARAT DENGAN SPATIAL AUTOCORRELATION: MEMPERSIAPKAN MOMENTUM PUNCAK BONUS DEMOGRAFI - Barwanto, Lutfhi Ahmad; Ramadhan, Afrizal (CREATIVE RESEARCH JOURNAL, 2024)
West Java is the most populated province in Indonesia, and this places quite a heavy burden in facing the wave of demographic dividend which is predicted to occur in 2030-2035. This article aims to identify patterns of similarity and anomalous values from West Java demographics using spatial autocorrelation. The data used consists of population growth rates at the Regency/City level in West Java as well as growth factors such as birth rates (TFR), infant mortality (IMR), and migration. To identify spatial patterns from demographic variables, Global Moran statistics and Local Indicators of Spatial Association (LISA) with the ArcMap application are used. The results show that there is global and local spatial autocorrelation for the demographic variables considered. The use of LISA also shows the existence of clusters and outliers that are formed as well as an indication of their location in West Java. The contribution of this study is to provide an overview of significant locations in West Java for policy studies and further research in preparing for the momentum of the demographic dividend.